Pengembangan Sistem Informasi Aplikasi Formulir Berbasis Web Menggunakan Php Pada Department Administrasi Pt United Tractors Tbk-Samarinda - Endah Rahmawati; Ahmad Nugraha Poernamawan; Sayekti Haris Suryawan (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
This service discusses the development of a web-based Form Application Information System using PHP in the Administration Department at PT United Tractors Tbk-Samarinda. This company faced difficulties in administering the employee claim form, where the form had to be submitted to the department head for approval. Obstacles that often arise include the absence of an approval official, company policies to reduce paper use, and human error. The development of this form application uses data collection methods through observation and interviews. Php was chosen as a programming language because of its flexibility and ability to be developed dynamically. MySQL is used as a database, while HTML and CSS are used to organize the structure and appearance of web pages. By implementing this system, the employee claim form process at PT United Tractors Tbk-Samarinda can make a positive contribution to the company's administrative efficiency.)